Vias de sinalização intracelular envolvidas no efeito proliferativo de relaxina em células de sertoli - Nascimento, Aline Rosa [UNIFESP] (2011)
Relaxin is an insulin-related peptide that activates the G-protein coupled receptor RXFP1. Although relaxin plays an important role in female reproduction its physiological role in the male reproductive system is still unclear. We have previously demonstrated that relaxin and RXFP1 are expressed in testis (FILONZI et al., 2007; CARDOSO et al., 2010). Both relaxin and RXFP1 have been immunolocalized to Sertoli and germ cells, suggesting that relaxin may be important for spermatogenesis. In fact, relaxin induced proliferation of Sertoli cells in culture. G-protein coupled receptors may activate cell proliferation by several mechanisms: transactivation of tyrosine kinase receptors and/ or activation of intracellular signaling kinases that culminates in the activation of MAP Kinase (ERK1/2) or PI3K pathway. The aim of the present study was to investigate the signaling events that lead to the proliferative response of relaxin in rat Sertoli cells. Primary culture of Sertoli cells was obtained from 15-day old Wistar rats. Cells were incubated in the absence or presence of increasing concentrations of relaxin (25-200 ng/ml), for different periods (5, 10, and 30 min), at 35°C. To characterize upstream pathways to ERK1/2 phosphorylation, cells were previously treated with the inhibitor of MEK1/2, U0126 (20 ìM for 30 minutes; N=3); the inhibitor of the kinase activity of the EGF receptor (EGFR) AG 1478 (1 ìM for 15 minutes; N=4); the inhibitor of Src family of tyrosine kinases, PP2 (5 nM for 30 minutes; N=4); the inhibitor of metalloproteases, GM 6001 (200 nM for 30 minutes; N=4); the PI3K inhibitor, wortmannin (100 nM for 30 minutes; N=5); the inhibitor of PKA, H89 (2 ìM for 2 hours; N=5); the general PKC inhibitor, GF 109203X (5 ìM for 30 minutes; N= 3) or the inhibitor of Gi/o, pertussis toxin (PTX, 100 ng/ml for 16 h; N=2). ERK1/2 phosphorylation was determined by Western Blot analysis. Relaxin increased ERK1/2 phosphorylation in a time and concentration-dependent fashion. The peak of ERK1/2 phosphorylation occurred at 5 minutes, and with 50 ng/ml of relaxin (N=3). ERK1/2 phosphorylation induced by relaxin was inhibited by pre-treatment with AG 1478, PP2, wortmannin, GF 109203X and pertussis toxin, but not with H89 and GM 6001. The effect of relaxin on Sertoli cell proliferation was determined by incubation of the cells with 50 ng/ml relaxin, for 24 hours, and by determination of the methyl [3H] thymidine incorporation, in the absence or presence of key inhibitors of the ERK1/2 pathway. Celll proliferation mediated by ERK1/2 was inhibited by the MEK1/2 inhibitor, UO126, and by the PI3K inhibitor, wortmannin. Other inhibitors of the ERK1/2 pathway such as the PKC inhibitor GF 109203X and the inhibitor of the tyrosine kinase of EGFR, AG1478, were not effective. Our results suggest that relaxin stimulates ERK1/2 phosphorylation and PI3K pathways, and that PI3K plays a central role in relaxin mitogenic effect in Sertoli cells. We propose the following sequence of events for the stimulatory role of relaxin in Sertoli cell proliferation: coupling of the stimulated RXFP1 with a Gi protein, release of âã subunits and activation of PI3K, which in turn can phosphorytale and activate PKC, Src and Ras. All these pathways can lead to Raf/MEK/ERK activation, and Src can phosphorylate EGFR, which may also contribute to ERK1/2 activation. ERK1/2 may regulate transcription of genes related to cell cycle regulation. Alternatively, PI3K may also activate transcription of genes that regulate the cell cycle. Further studies are necessary to clarify the mechanisms involved in the cell cycle regulation and cell proliferation induced by relaxin. This event certainly plays a central role in spermatogenesis and male (in)fertility and relaxin emerges as a novel paracrine/autocrine hormone that regulates Sertoli cell function.